1997
DOI: 10.1128/iai.65.12.5096-5102.1997
|View full text |Cite
|
Sign up to set email alerts
|

Virulence characteristics of oral treponemes in a murine model

Abstract: This study was designed to investigate the virulence characteristics of Treponema denticola, T. socranskii, T. pectinovorum, and T. vincentii following challenge infection of mice. These microorganisms induced welldemarcated, dose-dependent, raised subcutaneous (s.c.) abscesses which were similar in time of onset, lesion progression, and duration of healing. Only viable cells were capable of inducing these characteristic s.c. abscesses. Histological examination of the skin lesion 3 and 5 days postinfection rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…Dentilisin activity degrades the extracellular matrix, which is formed of collagen IV, ¢bronectin, and laminin [20,38], and may play a key role in the invasion. T. denticola invaded the surrounding tissues in a mouse abscess model [39,40]. These ¢ndings support our hypothesis that dentilisin plays a role in the invasion of host tissues by hydrolyzing the surrounding substance.…”
Section: Cytotoxicitysupporting
confidence: 85%
“…Dentilisin activity degrades the extracellular matrix, which is formed of collagen IV, ¢bronectin, and laminin [20,38], and may play a key role in the invasion. T. denticola invaded the surrounding tissues in a mouse abscess model [39,40]. These ¢ndings support our hypothesis that dentilisin plays a role in the invasion of host tissues by hydrolyzing the surrounding substance.…”
Section: Cytotoxicitysupporting
confidence: 85%
“…Interestingly, there was no effect on abscess formation in mice. This would suggest that the trypsin-like protease activity of the oral treponemes differs from that found in Porphyromonas gingivalis and appears to have a negligible functional role in this measure of virulence in vivo (31).…”
Section: A Murine Model Of Virulence Characteristics Of Oral Treponemesmentioning
confidence: 96%
“…Note that neither heatkilled nor formalin-killed cells were capable of inducing lesions with characteristics similar to those induced by viable bacterial infection. T. vincentii produced abscesses that were significantly larger than those noted for other oral treponemes (31). It has been suggested that T. vincentii is associated with a more tissue-invasive disease affecting the periodontium and that this microorganism can be detected deep within the periodontal tissues (29).…”
Section: A Murine Model Of Virulence Characteristics Of Oral Treponemesmentioning
confidence: 99%
“…These capacities are attributed to its virulence factors, including its LPS (lipopolysaccharide) (Bainbridge et al, 2002) and gingipains (Curtis et al, 2001). The gingipains, in particular, are a group of cysteine protease enzymes, believed to be the major endopeptidases produced by the bacterium (Kesavalu et al, 1997), as they represent the majority of the outer surface protein on P. gingivalis W50 (Veith et al, 2002). These are mainly the Arg-X and the Lys-X gingipains (Curtis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%